Grape VOCs Response to Postharvest Short-Term Ozone Treatments - Río Segade, Susana; Vilanova, Mar; Pollon, Matteo; Giacosa, Simone; Torchio, Fabrizio; Rolle, Luca (Frontiers in Plant Science, 2018)
Ozone has been recently recognized as an efficient sanitizing agent in wine industry because of its powerful oxidizing properties. Furthermore, postharvest treatments of grapes with ozone can stimulate defense responses by synthetizing secondary metabolites against oxidative stress. In this study, the effect of postharvest short-term ozone treatments was assessed for the first time on free and glycosylated volatile organic compounds (VOCs) of winegrapes. Two different ozone concentrations (30 and 60 μL/L) and exposure times (24 and 48 h) were investigated just after treatment (fresh grapes) and after partial dehydration up to 20% weight loss (withered grapes). The study was carried out on Moscato bianco winegrapes (Vitis vinifera L.) due to the importance of terpenes in white aromatic cultivars to produce high quality wines. The results obtained showed that short-term ozone treatment caused a significant decrease in total contents of free VOCs in fresh grapes, mainly due to terpenes. Among them, linalool, geraniol, and nerol are the major aromatic markers of Moscato bianco grapes. Ozone entailed a significant decrease of free linalool contents in fresh grapes, the less stressful ozone treatment showing the smaller linalool degradation. However, the stronger and longer ozone treatment induced the synthesis of this compound probably in response to higher abiotic stress. Instead, significant changes were not observed in geraniol and nerol contents in fresh grapes. This last ozone treatment also reduced the loss of free linalool by water loss in withered grapes even though total VOCs and terpenes remained relatively stable. Furthermore, ozone seems to promote the synthesis of free (+)-4-carene and 4-terpineol in withered grapes under certain treatment conditions. Regarding glycosylated compounds, total VOCs and terpenes were less sensitive to ozone. Our findings highlight that ozone can be used as sanitizing agent in aromatic grape varieties prior to winemaking without affecting sharply the aromatic profile of fresh grapes and even improving it in withered grapes.